2018
DOI: 10.1371/journal.pone.0190951
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic stress reactivity and craving in individuals with problematic Internet use

Abstract: The link between autonomic stress reactivity and subjective urge/craving has been less systematically examined in behavioral addictions (i.e. problematic Internet use) than in substance use disorders. The present study investigated whether problematic Internet users (PU) show enhanced autonomic stress reactivity than non-PU, indexed by lower Heart Rate Variability (HRV) and higher Skin Conductance Level (SCL) reactivity during the Trier Social Stress Test (TSST), whether greater reactivity is related to strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 60 publications
1
20
2
5
Order By: Relevance
“…To more accurately assess ANS function, it may be useful to measure HRV responses to particular stimuli as well as during the resting state, as this better reflects the ability of the ANS to respond appropriately and adaptively to environmental change ( 9 ). A previous study on Internet addiction showed that individuals with problematic Internet use had a lower standard deviation of the R-R interval (SDNN, reflects overall HRV levels) than non-problematic users during rest but not during and after the Trier social stress test (TSST) ( 10 ). This measure could be applied to assess HRV responses to gaming-related stimuli rather than general stress stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…To more accurately assess ANS function, it may be useful to measure HRV responses to particular stimuli as well as during the resting state, as this better reflects the ability of the ANS to respond appropriately and adaptively to environmental change ( 9 ). A previous study on Internet addiction showed that individuals with problematic Internet use had a lower standard deviation of the R-R interval (SDNN, reflects overall HRV levels) than non-problematic users during rest but not during and after the Trier social stress test (TSST) ( 10 ). This measure could be applied to assess HRV responses to gaming-related stimuli rather than general stress stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, heart rate variability is positively associated with the ability to regulate one’s eating behavior ( Meule et al, 2012a , b ). In fact, higher levels of sympathetic activation, as measured by decreased heart rate variability, may be associated with increased levels of craving and decreased self-regulation ( Quintana et al, 2013 ; Moretta and Buodo, 2018 ). Taken together, this suggests that as anxiety increases and heart rate variability decreases, one would expect to see a corresponding decrease in self-regulation and in the ability to resist unhealthy food cravings.…”
Section: Discussionmentioning
confidence: 99%
“…La relación del UPI con el abuso de alcohol ha sido estudiada por distintos autores, llegando a la conclusión de que existe cierta correlación positiva (Yau, Potenza y White, 2013;Bibbey et al, 2015;Rücker et al, 2015;Kim et al, 2016;Wartberg et al, 2016;Hricová, Paulisová y Orosová, 2016;Golpe et al, 2017;Morioka et al, 2017;Müller y Montag, 2017;De Vries et al, 2018;Moretta y Buodo, 2018;Grover et al, 2019). El instrumento de recogida de datos más utilizado para medir el abuso de alcohol ha sido The Alcohol Use Disorders Identification Test (AUDIT), aplicado en 80 % de los casos.…”
Section: Abuso De Alcoholunclassified
“…La patología estrés ha sido estudiada por distintos trabajos que lo asocian con un UPI (Thomée, Härenstam y Hagberg, 2012;Derbyshire et al, 2013;Park, 2014;Bibbey et al, 2015;Dutta y Yen, 2017;Odaci y Çikrikci, 2017aOdaci y Çikrikci, , 2017bMoretta y Buodo, 2018;Liao, Chen y Lin, 2018;Grover et al, 2019). En cuanto a los instrumentos de recogida de datos, destaca Perceived Stress Scale (PSS) (70 %), Maslach Burnout Inventory (MBI), Trier Social Stress Test (TSST), The Academic Expectations Stress Inventory (AESI) (10 %).…”
Section: Estrésunclassified